Kualitas Perairan di Daerah Fishing Ground Nelayan Kerang di Pesisir Timur Kota Semarang - Chrisna Adhi Suryono; Baskoro Rochaddi (Universitas Diponegoro, 2017)
This study aimed to assess the relationship between marine water qualities in bivalve fishing ground on easter part of Semarang coastal water. The result of study shows that the waters quality on those areas is still available for marine organism life. The water quality of dissolved oxygen between 5,6 – 6,2 ppm, water temperature 29,3 – 30,4 oC, salinity 32 – 33,7 ppt, pH 7,1 – 7,8, turbidity 20,2 – 42,5 NTU, and current velocity 0,15 – 0,55 m/sec. That water quality in the study areas compered with standard water for marinr life is still to suport marine bivalvia to live. Its is proved with some of bivalve found for examples (Anadara granosa A. pilula, A. Gubernaculum, A. Inaequivalvis, Pharella javanica, Paphia undulate, Marcia hiantina, Harvella plicataria, Mactra violacea dan Placuna placenta) Hasil penelitian menunjukan bahwa kualitas air laut didaerah penelitian masih dikatan layak untuk kehidupan organisme laut. Konsentarsi DO (5,6 – 6,2 ppm), suhu air (29,3 – 30,4 oC), salintas (32 – 33,7 ppt), pH (7,1 – 7,8), kekeruhan (20,2 – 42,5 NTU) dan kecepatan arus (0,15 – 0,55 m/det). Bila dibandingkan dengan baku mutu air laut untuk kehidupan organisme laut secara keseluruhan masih layah terbukti ditemukanya beberapa jenis kerang seperti Anadara granosa A. pilula, A. Gubernaculum, A. Inaequivalvis, Pharella javanica, Paphia undulate, Marcia hiantina, Harvella plicataria, Mactra violacea dan Placuna placenta.